THE BIAS OF WEB BASED RAIN GAUGE CALIBRATOR DUE TO BUBBLES - Sensus Wijonarko; Dadang Rustandi; Tatik Maftukhah; Mahmudi Mahmudi; Bernadus H Sirenden; Jalu Ahmad Prakosa; Purwowibowo Purwowibowo (LIPI Press, Anggota IKAPI, 2020)
This study was devoted to investigate the bias due to entrapped air - in the cylindrical tube water - to a web based rain gauge calibrator (WBRGC). This study was carried out in laboratory temperature around 25 °C using experiment method, especially by comparing the massof the water with and without bubbles. The entrapped airusedthe space for1.57 gof 1009 g ofwater if there were no bubbles, so this condition madebiasaround - 0.16 %.This bias was very significant in contributing the uncertainty of WBRGC, where in this case was 3 ml for 966 ml of water (0.31 %). Hence, this bias should be promptly overcome.